Compost and biochar application to acidic soils in a hot submoist tropical environment improves the forage yield and quality of Desho grass (Pennisetum pedicellatum Trin.) - Seyifu Shifa; Mohammed Worku; Abegaz Beyene (All Life)
Biochar use improves soil quality and plant growth, especially when it is coapplied with organic fertilizers. However, its effect on forage yield and quality is unknown. The effects of compost and coffee-husk biochar application at different rates on the biomass production and chemical composition of Desho grass in acidic soils in a tropical environment were examined to test the synergetic impact of compost and biochar on forage yield and quality and to identify the best coapplication rates for forage production. The economic benefits of the treatments also analyzed. Compost and biochar application considerably improved biomass production and organic matter (OM) and crude protein (CP) contents but reduced dry matter, ash and fiber contents. In particular, compost and biochar coapplication at full rates (4.5 and 5.0 t ha−1, respectively) produced the highest fresh and dry biomasses and OM and CP contents and the lowest ash and fiber contents. However, compost and biochar coapplication at half rates (2.25 and 2.5 t ha−1, respectively) provided the greatest economic benefit, while compost applied alone provided the least economic benefit. This study highlights the synergetic effect of compost and biochar cousage on the yield and quality of Desho grass forage.